Urbanization Is Associated with Divergence in Pace-of-Life in Great Tits - Charmantier, Anne; Demeyrier, Virginie; Lambrechts, Marcel; Perret, Samuel; Grégoire, Arnaud (Frontiers in Ecology and Evolution, 2017)
As an extension of the classic life history theory, the recently highlighted pace-of-life syndrome hypothesis predicts the coevolution of behavioural, physiological and life-history traits. For instance, bolder and shyer individuals do not only differ in personality profiles, but also in neuro-endocrinology and breeding patterns. While theory predicts that bolder (i.e. proactive), more aggressive individuals should colonize more rapidly urbanized habitats than shyer (i.e. reactive), less aggressive individuals, it is also predicted that across generations, adaptive selection processes could favour shyer individuals that are more sensitive to novel environmental cues. Here we compared two personality traits (handling aggression, exploration score in a novel environment), one physiological trait related to stress response (breath rate) and four breeding traits (lay date, clutch size, hatching success and fledging success) in a rural and an urban study population of Mediterranean great tits Parus major. Mixed models revealed strong phenotypic divergence between forest and city in most traits explored, in particular in personality, whereby urban great tits were more reactive to stress and faster explorers compared to rural birds (yet not more aggressive). Urban birds also laid smaller broods earlier in spring compared to their rural conspecifics, and city broods resulted in lower hatching success yet interestingly fledging success was similar. Nest-box centered measures of anthropogenic (artificial light, pedestrians and cars) perturbation and resource abundance allowed us to go beyond the classical forest/city comparison by exploring the phenotypic variation across an urbanization gradient. This revealed that high urbanisation in nest-box surroundings was associated overall with earlier breeding and smaller clutches, but also with faster breath rate, although these trends showed strong annual variation. Ongoing rapid urbanization and non-random gene flow between rural and urban great tits could both contribute to the high prevalence of bold breeders in the city. Our study suggests the existence of urban and rural great tit ecotypes with different pace-of-life, but also a finer-scale divergence along the degree of urbanisation within the city. Future studies are required to determine whether this phenotypic variation at different spatiotemporal scales is adaptive and whether it has a genetic basis or results from phenotypic plasticity.